KEWENANGAN PENGAWASAN DAN ADVOKASI KOMISI YUDISIAL TERHADAP HAKIM BERDASARKAN UNDANG-UNDANG NO. 18 TAHUN 2011 PERUBAHAN ATAS UNDANG-UNDANG NO. 22 TAHUN 2004 TENTANG KOMISI YUDISIAL - NI LUH ARININGSIH SARI (Universitas Mahasaraswati K. Mataram, 2022)
The purpose of this study is to find out how the form of supervision and advocacy carried out by the Judicial Commission against Judges based on Law no. 18 of 2011 concerning Amendments to Law No. 22 of 2004 concerning the Judicial Commission. This research is a type of normative legal research. Whereas Article 24B paragraph (1) of the 1945 Constitution has explicitly stated that the Judicial Commission is an independent State institution that is given the authority to select candidates for Supreme Court Justices and authorities in the context of maintaining and upholding the honor, dignity and behavior of judges (Judicial Commission as external supervisor of Judge). Meanwhile, the Supreme Court is an internal supervisor based on Article 39 of Law No. 48 of 2009 concerning Judicial Power. The Judicial Commission advocates for judges with the issuance of the Indonesian Judicial Commission Regulation No. 8 of 2013 concerning Judge Advocacy